Robust Decentralized Fuzzy Controller Design for Nonlinear Large-Scale Interconnected Descriptor Systems - Chang, Wen-Jer; Su, Che-Lun; Pen, Chin-Lin; Lin, Zi-Yao (Journal of physics. Conference series, 2022)
This paper dealt with the robust control problem for fuzzy large-scale descriptor systems (FLSDS) with uncertainties. First, each nonlinear subsystem of the large-scale descriptor system was described as a FLSDS with interconnectivity and uncertainty. Based on the proportional-plus-derivative state feedback (PD) method, the decentralized fuzzy controller in each subsystem was designed to stabilize the whole system. In order to solve the uncertainties problem in the control system simply, a benefits robust approach has been proposed. The final stability conditions can be recast into the linear matrix inequality (LMI) problem by the Schur complement. At last, a numerical example was given to illustrate the control design procedure and its effectiveness.